2021
DOI: 10.1037/cou0000545
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual dynamics between alliance and symptom severity in long-term psychotherapy: Why time matters.

Abstract: Objective: The association between alliance and therapy outcome is one of the most investigated factors in psychotherapy research. However, even studies using advanced methods estimate effects over a specific time period (interval) between measurement occasions. Thus, it remains unknown how the magnitude and direction of effects depend on the considered time interval, resulting in limited comparability across studies. The current study examines the influence of time on the within-person relationship between al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…There is preliminary evidence from studies examining within‐patient effects that the alliance may have a causal role in improving outcomes 32 , including studies of PDT (in depressive disorders) 85 . Specifically for PDT, it has been documented that the temporal precedence of alliance predicting symptom change becomes stronger with time over the course of long‐term therapy 86 .…”
Section: Resultsmentioning
confidence: 99%
“…There is preliminary evidence from studies examining within‐patient effects that the alliance may have a causal role in improving outcomes 32 , including studies of PDT (in depressive disorders) 85 . Specifically for PDT, it has been documented that the temporal precedence of alliance predicting symptom change becomes stronger with time over the course of long‐term therapy 86 .…”
Section: Resultsmentioning
confidence: 99%
“…Measuring the alliance repeatedly throughout treatment might reveal more complex relationships between guidance, working alliance and outcome. Such studies might reveal whether the importance of working alliance varies throughout treatment, as has been done for face-to-face psychotherapies (e.g., Volz et al, 2021 ). Fourth, the study had dropout rates at post-treatment of 31.1 %.…”
Section: Discussionmentioning
confidence: 99%
“…From a theoretical perspective, agency and therapeutic bond might build up over the course of treatment as patient and therapist get to know each other and define their roles in the therapeutic process. Regarding the alliance, it was recently shown that associations between alliance and outcome are the strongest for time intervals of up to 40 sessions (Volz et al, 2021). To depict these processes, we thus intended to conduct our study in long-term treatments.…”
Section: Data Transparencymentioning
confidence: 99%